2007
DOI: 10.1136/oem.2006.032243
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial evaluating an alternative mouse and forearm support on upper body discomfort and musculoskeletal disorders among engineers

Abstract: In engineers who use a computer for more than 20 h per week, a forearm support board may reduce right upper extremity discomfort attributed to computer use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 30 publications
(34 reference statements)
1
52
0
2
Order By: Relevance
“…A study of 206 engineers used a 10-point scale to report pain severity similar to the one used in our study (42). Compared to our call center employees, these engineers (who had more control of their work tasks than call center operators) reported lower pain severity in the neck-shoulder (1.9 versus 2.4), right upper extremity (1.7 versus 2.3), and left upper extremity (0.7 versus 1.5).…”
Section: Prevalence Of Effort-reward Imbalancementioning
confidence: 99%
“…A study of 206 engineers used a 10-point scale to report pain severity similar to the one used in our study (42). Compared to our call center employees, these engineers (who had more control of their work tasks than call center operators) reported lower pain severity in the neck-shoulder (1.9 versus 2.4), right upper extremity (1.7 versus 2.3), and left upper extremity (0.7 versus 1.5).…”
Section: Prevalence Of Effort-reward Imbalancementioning
confidence: 99%
“…Alternative input devices are often used as an intervention to reduce the risk of developing musculoskeletal symptoms or musculoskeletal disorders (Conlon, Krause, & Rempel, 2007;Rempel et al, 2006). Alternative input devices that promote a more neutral forearm posture (less pronation) are found to reduce pain in the upper extremity (Aarås, Dainoff, Ro, & Thoresen, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A one year randomized controlled trial found a prevention effect of arm support use in 182 call center operators (Rempel et al, 2006). However, Conlon et al (2008) found the opposite with no effect of forearm support on musculoskeletal symptoms of the neck and shoulder.…”
Section: Workplace Physical Risk Factorsmentioning
confidence: 99%
“…A one year randomized controlled trial found a prevention effect of arm support use in 182 call center operators (Rempel et al, 2006). However, Conlon et al (2008) found the opposite with no effect of forearm support on musculoskeletal symptoms of the neck and shoulder.Other features of an office worker's workstation that may impact on the mechanical load placed on the neck or shoulder muscles include the position of the keyboard on the desk top (Kotani et al, 2007) and location of hard copy documents (Goostrey et al, 2014) with the desk top the least optimal location for documents in terms of requiring the greatest neck movement and muscle activity.Variations in the way computer work is performed may also strain the musculoskeletal system. A more rapid pace of work in stressful conditions is associated with increased muscle activity of the trapezius and extensor digitorum muscles (EMG studies), increased force applied to the computer mouse, increased heart rate, and increased blood pressure (Grace P.…”
mentioning
confidence: 99%
See 1 more Smart Citation